Chitosan-coated bovine serum albumin nanoparticles for topical tetrandrine delivery in glaucoma: in vitro and in vivo assessment - Salma El-Sayed Radwan; Riham M. El-Moslemany; Radwa A. Mehanna; Eman H. Thabet; Elsayeda-Zeinab A. Abdelfattah; Amal El-Kamel (Taylor & Francis Group, 2022)
Glaucoma is one of the leading causes of blindness. Therapies available suffer from several drawbacks including low bioavailability, repeated administration and poor patient compliance with adverse effects thereafter. In this study, bovine serum albumin nanoparticles (BSA-NPs) coated with chitosan(CS) were developed for the topical delivery of tetrandrine (TET) for glaucoma management. Optimized nanoparticles were prepared by desolvation. pH, BSA, CS and cross-linking agent concentrations effects on BSA-NPs colloidal properties were investigated. CS-BSA-NPs with particle size 237.9 nm and zeta potential 24 mV was selected for further evaluation. EE% exceeded 95% with sustained release profile. In vitro mucoadhesion was evaluated based on changes in viscosity and zeta potential upon incubation with mucin. Ex vivo transcorneal permeation was significantly enhanced for CS coated formulation. In vitro cell culture studies on corneal stromal fibroblasts revealed NPs biocompatibility with enhanced cellular uptake and improved antioxidant and anti-proliferative properties for the CS-coated formulation. Moreover, BSA-NPs were nonirritant as shown by HET-CAM test. Also, bioavailability in rabbit aqueous humor showed 2-fold increase for CS-TET-BSA-NPs compared to TET with a sustained reduction in intraocular pressure in a rabbit glaucoma model. Overall, results suggest CS-BSA-NPs as a promising platform for topical ocular TET delivery in the management of glaucoma.